Amino Acids Content in Different Cultivars of Young Radish (Raphanus sativus) - Kim, Jae Kwang; Bong, Sun Ju; Park, Sang Un (Asian Journal of Chemistry, 2017)
The variations in the amino acid contents of five different Korean cultivars of young radish were investigated in this study. Twenty-one amino acids were detected among the different cultivars and the presence and quantity of amino acids varied greatly among the cultivars. The cultivar Martjjang contained the highest total quantity of amino acids, with values 3.65, 2.26, 2.10 and 1.80 times higher than the total amino acid content in the Saebaram, Chuha, Chudong and Super Red cultivars, respectively. Martjjang also contains the highest levels of all amino acids except for a few. The levels of leucine, lysine, g-amino butyric acid, asparagine and alanine were much higher in the Martjjang cultivar, which had 23.58, 12.01, 3.71, 3.16 and 2.83 times higher concentrations of these amino acids, respectively, than the Saebaram cultivar, which had the lowest content. In all cultivars, the amino acids aspartate, serine, glycine, threonine, cysteine, valine, methionine, phenylalanine and isoleucine were found in moderate quantities, with Martjjang containing the highest quantity of each. The levels of aspartate, serine, glycine, threonine, cysteine, valine, phenylalanine and isoleucine in Martjjang were 3.83, 5.39, 2.10, 5.22, 4.31, 6.58, 5.02 and 9.36 times higher, respectively, than those in the Saebaram cultivar, which had the lowest concentrations of these amino acids. The levels of vitamin U, glutamine and histidine were the lowest irrespective of cultivar, with Martjjang containing the highest quantity of each except histidine. The cultivar Super Red contains the second highest quantity of total amino acids (738.26 mg/100 g dry wt.), where only histidine and arginine were found in the highest quantities. In conclusion, the present results demonstrate that Korean young radish cultivars contain variable quantities of amino acids, while the Martjjang cultivar showing the greatest potential to serve as a commercial source of amino acids.